Maternal and perinatal outcomes in cases of antepartum haemorrhage: a 3-year observational study in a tertiary care hospital - Samal, Sunil Kumar; Rathod, Setu; Rani, Reddi; Ghose, Seetesh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The leading cause of maternal mortality in world is obstetric haemorrhage. Antepartum haemorrhage (APH) is defined as bleeding from or into the genital tract after 28weeks of pregnancy and before delivery of the baby. The aim of the present study is to study the demographic profile, type of antepartum haemorrhage (APH), maternal and perinatal complications in cases of APH and to formulate preventive guidelines so as to reduce maternal and perinatal complications in cases of APH. Methods: The study was a retrospective observational study conducted in Mahatma Gandhi Medical College & Research Institute, Pondicherry from November 2013- October 2016 [3 years]. Cases of pregnancy complicated with APH were taken. Cases with bleeding before 28 weeks and after delivery of the baby were excluded. Data collected from the records present in Labour ward complex and Medical record section. Statistical analysis done by using SPSS software version 21. Results: Total 218 cases were presented with APH and the incidence was 2.9%. Among these 49.5% were Placenta Praevia, 42.2% were abruption placentae, 6.8% cases were indeterminate (3 cases of vasa praevia and 12 cases of excessive show) and 1.5% cases were of extraplacental cause(Local causes). Most cases were multipara with most common age group was 26-30 years (42.2%). Pregnancy in most of the cases was terminated during 34-36+6 weeks of gestation (73.0%). Most common associated risk factors found were previous caesarean section, preeclampsia, previous history of curettage, malpresentation and anaemia. Postpartum haemorrhage was found in 42.2% cases while in 4 cases peripartum hysterectomy done. Most common perinatal complications were due to low birth weight (66.5%). Conclusions: The morbidity and mortality in pregnancies complicated with APH can be achieved by early diagnosis, proper antenatal planning and terminating the pregnancy in a well-equipped tertiary health care centre.